The Role of Carbon Emission Disclosure in Moderating Profitability and GCG on Firm Value in Indonesia - Tedja, The Wechen Abraham; Stephanus, Daniel Sugama; Suganda, Tarsisius Renald; Pratama, Bagas Brian (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2025)
This study aims to examine the relationship between profitability and good corporate governance (GCG), measured through independent commissioners, institutional ownership, managerial ownership, and gender diversity, on firm value, with carbon emission disclosure as a moderating variable. This study employs the panel data regression method using a sample of energy sector companies listed on the Indonesia Stock Exchange from 2019 to 2023.  The findings suggest that profitability significantly enhances firm value, whereas independent commissioners and gender diversity have a negative impact. On the other hand, institutional ownership and managerial ownership do not show any effect. Additionally, carbon emission disclosure can positively moderate the relationship between independent commissioners, institutional ownership, and gender diversity with firm value. However, carbon emission disclosure negatively moderates the relationship between profitability and managerial ownership with firm value. The findings of this study can serve as a reference for companies in addressing environmental responsibility disclosures and provide recommendations for the government to consider policies regarding carbon emission disclosure in sustainability reporting.